Oxford and Paris University manuscripts in the thirteenth century - Patterson, S (1969)
The purpose of this thesis is to find a method for differentiating the manuscripts of the Universities of Paris and Oxford in the thirteenth century by the study of the decoration of flourished initials. In order to study the decoration I analysed it by separating it into its component parts. I then codified the results and listed them in a Catalogue of Components. This enabled me to differentiate manuscripts and to date them in a particular period. The thirteenth century was chosen for this work as being the period when the manuscripts of the two Universities most resembled each other. It is possible that Oxford University evolved from an exodus of students from Paris in the latter part of the twelfth century, as suggested by Rashdall. 'This and a continuing exchange of students between the two Universities (which Rashdall further suggests), could explain the similarities of manuscripts of the two centres. The similarities could have come about in these ways: the students would have brought books with them,the whole style and production of which could have influenced those produced in the new centre; any new books written by a scribe or student trained in either of the Universities would almost certainly have reflected the influence of that university; and a scribe's style could have influenced the style of books produced in the centre where he settled, worked and possibly taught his techniques. But there is an obvious difficulty in deciding whether a book reflects the style of one University or another: it is impossible to tell whether, for example, a book was written in Paris, or in Oxford by a scribe trained in Paris. Continued in thesis ...